Thermal Performance Analysis of a Newly Designed Circular Firewood Boiling Salt Stove - Apichart Srichat; Weerapol Kaewka; Ponthep Vengsungnle; Songkran Wiriyasart; Paisarn Naphon (Journal of Engineering and Technological Sciences, 2021)
Different biomass stoves are introduced and distributed among people living in rural and urban areas, especially in developing countries. For salt crystal production in Thailand’s rural north-eastern area, open fire stoves are used in domestic and small productive activities. Their thermal efficiency is very low for converting heat into utilization energy. A new stove with a circular configuration was designed and constructed to consider its thermal efficiency and economics, which were compared with those from a traditional and an improved traditional stove. The obtained thermal efficiency of the newly designed stove was 14.77% higher than that of the improved stove and 81.45% higher than that of the traditional stove. For the same initial saline volume, the final amounts of salt crystals and salt flowers obtained from the newly designed stove was higher compared with those obtained from the improved stove and the traditional stove, respectively, resulting in a 69.25% shorter payback period.